Control and accountability in supply chain management: Evidence from a South African metropolitan municipality - Modeni Mudzamba Sibanda; Beauty Zindi; Tafadzwa Clementine Maramura (Cogent Business & Management, 2020)
Accountability requires supply chain management (SCM) public officials to account for, report on, explain and justify activities, and accept responsibility for municipal financial expenditure outcomes. Regardless of having SCM systems in place, efficiency in terms of procuring, tendering and sourcing goods and services in South African municipalities remains problematic. A key contributory factor to regressions in local government audit outcomes is the constant failure to develop, implement and monitor effective SCM systems, oversight, internal controls and financial reporting processes. With recurring instances of fruitless, irregular and wasteful expenditure, compliance with SCM policies, regulations and legislative frameworks needs solidification. When effectively implemented, control and oversight measures reduce waste, eradicates ethical malfeasance and promotes, integrity, transparency and accountability. The purpose of this article is to determine the SCM, risk factors that threaten accountability and how they can be mitigated in a typical South African Metropolitan Municipality. This descriptive and explanatory qualitative case study collected interview data from a purposeful sample of 14 (n = 14) information-rich participants. Secondary data were also collected from official documents and extant literature. Results indicate weak implementation of internal audit controls and policies, which make it challenging for internal audit and oversight committees to timely detect unethical, unfair, inequitable, opaque, uncompetitive and cost-inefficient SCM practices. The consequences are pervasive non-compliance with SCM policy, procuring and tendering processes, favouritism and corruptible tendencies. These have to be timely mitigated so as to remedy risks in the SCM process, which constrain municipal financial accountability.
Keywords: 650; supply chain management; accountability; control; internal audit; oversight; contracting; South Africa